Comparison of Aspirin s Antioxidant Effect with Selenium and Vitamin E by Measuring Mitochondrial Selenium Dependent Glutathione Peroxidase and Cytosolic Total Glutathione Peroxidase Activity in Mice Liver - Cebi, Aysegⁿl; Diraman, Emine; Eren, Zafer (Asian Journal of Chemistry, 2010)
In this study, the antioxidant effect of aspirin was studied and comparedwith selenium and vitamin E on the activities of mitochondrial seleniumdependent glutathione peroxidase (Se-GPX) and cytosolic total glutathioneperoxidase (t-GPX). After the injection of selenium, vitamin Eand aspirin intraperitonally to the mice, they were killed by servicaldislocation at the 2, 4, 8, 12 and 24 h and their livers were removed.Enzyme fractions were obtained from livers. Mitochondrial fractionswere used to find out the changes in the Se-GPX activities and cytosolicfractions were used to find out the changes in the total GPX activity.Aspirin increased cytosolic t-GPX activity in 12 and 24 h and mitochondrialSe-GPX activity in 8 h when compared with controls (p < 0.05).The t-GPX activity was less than vitamin E in 2 h and selenium in 12 h(p < 0.05). The study shows that aspirin has an antioxidant effect byincreasing the cytosolic t-GPX and mitochondrial SeGPX activity. Theantioxidant effect of aspirin is less than selenium and vitamin E.